Study Of Heat-Physical Processes In Solar Dryers - Kahhorov, S.K.; Juraev, Kh.O.; Jamilov, Yu.; Khudoyberdiev, Sh.B. (The journal of contemporary issues in business and government, 2021)
This article raises the problem of studying the thermal and physical processes that take place in solar fruit dryers. Technological processes related to the quality of dried fruits in dryers were studied.